Interleukin-6 (IL-6), Interleukin-8 (IL-8), and Tumor Necrosis FactorAlpha (TNF-a): Their Role in the Development and Metastasis of Tumor Cells - Adnyana, I Gede Angga (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2019)
ABSTRACT: Cancer is a disease caused by uncontrolled and excessive cell division. The death caused by cancer is largely due to the cancer cell metastasis process. Cancer metastasis process is a consequence of molecules signaling pathways and interactions amongst cells in the body. Molecules involved and attributable to cancer metastasis are IL-6, IL-8, and TNF-Î±. This article aimed to describe the roles of IL-6, IL-8, and TNF-Î± in the process of various cancer cases.